Illuminating Indigenous health care provider stories through forum theater. (March 2021) - Van Bewer, Vanessa; Woodgate, Roberta L; Martin, Donna; Deer, Frank
Learning about the historical and current context of Indigenous peoples' lives and building campus communities that value cultural safety remains at the heart of the Canadian educational agenda and have been enacted as priorities in the Manitoba Collaborative Indigenous Education Blueprint. A participatory approach informed by forum theater and Indigenous sharing circles involving collaboration between Indigenous and non-Indigenous health care professionals ( n = 8) was employed to explore the above priorities. Through the workshop activities, vignettes were created and performed to an audience of students and educators ( n = 7). The findings emerging from the workshop illuminated that Indigenous people in nursing and higher education face challenges with negotiating their identity, lateral violence and struggle to find safe spaces and people due to tokenism and a paucity of physical spaces dedicated to Indigenous students. This study contributed to provoking a greater understanding of Indigenous experiences in higher education and advancing reconciliation.